Ultrasound Evaluation for Varicocele and its Relationship with Sperm Characteristics through Semen Analysis - Saeed, Ikhlas O.; Awad, Ibrahim A.; Eltyib , Hamad Elniel H. (Advances in Social Sciences Research Journal, 2020)
The safety of the reproductive organs has a great positive impact on the human psyche, so early and accurate diagnosis of scrotal disorders by ultrasound was one of the necessities that puts the individual in the correct path of treatment. This study was conducted to evaluate the significance of ultrasound imaging technology in the diagnosis of varicocele and its relationship with sperm characteristics through semen analysis. We retrospectively reviewed a total of 281 male patients who underwent scrotum ultrasound at King Abdul-Aziz University Hospital-Radiology Department between 2017 and 2019 with age range of (11-76) years. Ultrasound result showed 119 (42.3%) had varicocele. Semen analysis was performed for 143 patients and the results showed a significant correlation between sperm characteristics and varicocele disorder (p < 0.001). Imaging of the scrotum by ultrasound is of great importance in diagnosing various andrology diseases, including varicocele, which have clear effects on sperm count and motility.